2021
DOI: 10.1007/s10668-021-01402-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension of binary mixtures containing environmentally friendly ionic liquids: Insights from artificial intelligence

Abstract: The surface tension (ST) of ionic liquids (ILs) and their accompanying mixtures allows engineers to accurately arrange new processes on the industrial scale. Without any doubt, experimental methods for the specification of the ST of every supposable IL and its mixtures with other compounds would be an arduous job. Also, experimental measurements are effortful and prohibitive; thus, a precise estimation of the property via a dependable method would be greatly desirable. For doing this task, a new modeling metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…The relative performance of the four unimodal models on the training, internal, and external test sets showed that the AUCs of the T2WIFS, DWI, ADC, and CE-T1WI models on the training set were 0.84, 0.93, 0.96, 0.95, and 0.87, respectively. In the external test set, the DWI model has the highest AUC of 0.94, while the other three models are 0.91, 0.86, and 0.88, respectively [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The relative performance of the four unimodal models on the training, internal, and external test sets showed that the AUCs of the T2WIFS, DWI, ADC, and CE-T1WI models on the training set were 0.84, 0.93, 0.96, 0.95, and 0.87, respectively. In the external test set, the DWI model has the highest AUC of 0.94, while the other three models are 0.91, 0.86, and 0.88, respectively [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…So, a SA is the best way to achieve this goal. In this regard, they follow the relevancy factor, r, for every input variable as follows [65][66][67]:…”
Section: Resultsmentioning
confidence: 99%
“…The artificial intelligencebased tools, such as artificial neural networks (ANNs), were also applied to the estimation of the thermal and transport properties of the mixtures containing ILs for the development of innovative process technologies. 50,51 As is known, the thermophysical properties of fluids and their mixtures are fundamentally important for engineering applications. 52 Especially, density and viscosity data are essential in the development of process technology.…”
Section: Introductionmentioning
confidence: 99%
“…The artificial intelligence-based tools, such as artificial neural networks (ANNs), were also applied to the estimation of the thermal and transport properties of the mixtures containing ILs for the development of innovative process technologies. 50,51…”
Section: Introductionmentioning
confidence: 99%